Maritime Economic Development In Coastal And Island Areas (Case Study In Tayando Ohoiel Village, Tayando Tam District, Tual City) - Djodding, Ikram Mubarak; Arnold, Luturmas Wanlyeamin (Jurnal Mirai Management, 2024)
The economic potential of utilizing marine resources in Tayando - Ohoiel Village is very large and should be able to make a significant contribution to the regional economy, and even has the potential to become the main sector driving the economy. However, the maritime sector has not been utilized optimally, as can be seen from the contribution of the fisheries sector which is still low compared to the agricultural and plantation sectors, as well as the socio-economic conditions of communities related to the maritime sector which are still less than satisfactory. This research aims to identify policies that support maritime economic development as well as strategies to optimize this sector in Tayando - Ohoiel Village. The research results show that there are various policies that can support maritime economic development, such as regional economic development policies, fisheries policies, creative sector development policies, and regional infrastructure development policies. Various strategies can be implemented to optimize maritime economic development in Tayando - Ohoiel Village by exploiting existing potential and opportunities, so that the maritime sector can become a leading sector in regional economic development.